Study protocol of a randomised controlled feasibility study of food-related computerised attention training versus mindfulness training and waiting-list control for adults with overweight or obesity - Daniela Mercado; Jessica Werthmann; Iain C. Campbell; Ulrike Schmidt (Trials, 2020)
Abstract Background Obesity is a highly prevalent condition with multiple adverse health consequences. Widely available first-line treatments for obesity, such as dietary and other lifestyle interventions, typically have only short-term effects. Thus, new treatment approaches are needed. Novel interventions such as Attention Bias Modification Training (ABMT) and mindfulness-based interventions focus on modifying different maladaptive cognitive patterns typically present in people with obesity (e.g. attention bias to food cues); however, their mechanisms of action remain largely unknown. We describe the theoretical basis and the rationale for a study protocol of a feasibility randomised controlled trial (RCT) comparing two attention trainings (ABMT vs Mindfulness Training [MT]) in people with overweight or obesity. The aim of this study is to inform the development of a large-scale RCT in relation to acceptability and attendance rates and to identify preliminary evidence for the interventions’ clinical efficacy and potential underlying mechanisms. Design Forty-five adults who are either overweight or obese (minimum body mass index of 25 kg/m2) will be randomly allocated to receive eight sessions over eight weeks of either computerised ABMT or MT or be on a waiting list. Clinical and cognitive outcomes will be assessed at baseline, post-treatment (8 weeks) and follow-up (12 weeks post-randomisation). These include mood, body composition and attention biases. Credibility and acceptability of the trainings will be assessed using questionnaires, and recruitment and retention rates will be recorded. Discussion Findings will inform the feasibility of developing a large-scale RCT that takes into consideration effect sizes for primary outcome measures and the acceptability of the design. The study will also provide preliminary evidence on the clinical efficacy of two different attention trainings for people with obesity and associated underlying mechanisms. Trial registration ISRCTN Registry, ISRCTN15745838. Registered on 22 May 2018.